Improved Dry Eye Symptoms and Signs of Patients With Meibomian Gland Dysfunction by a Dietary Supplement - Liu, Kangcheng; Chan, Yau Kei; Peng, Xia; Yuan, Ruolan; Liao, Min; Liang, Jingwen; Tang, Xiangbo; Xu, Yi; Cai, Yingjun; Li, Qiangxiang; Wang, Hua (Frontiers in Medicine, 2021)
Purpose: To explore the therapeutic effect of a dietary supplement on dry eye with meibomian gland dysfunction (MGD). Methods: Sixty patients with MGD-related dry eye were included in this prospective and randomized, placebo-controlled study. All the subjects were treated with eye hot compress, artificial tears and antibiotic ointment. After that, the patients received dietary supplementary or placebo daily for 12 weeks. The dry eye signs, function of MG, and visual quality of the patients were assessed at 4, 8 and 12 weeks after the treatment. Results: 12 weeks after treatment, patients received dietary supplement had a significant better improvement of dry eye symptoms, in terms of ocular surface diseases index and tear breaking up time, than those who received placebo (P<0.05). The function of MG, in terms of meibum quality, MG exclusion and MG obstruction scores, was significantly improved in both dietary supplement and placebo groups (P<0.05). Patients received dietary supplement had a significant better improvement of the MG structure, in terms of acinar diameter and acinar density, than those who received placebo (P<0.05). The number of inflammatory cells near MG was significantly lower in the dietary supplement group when compared with the placebo group (P <0.05). The objective visual quality was significantly improved in dietary supplement group but not in the placebo group (P<0.05). Conclusion: The dietary supplement can effectively improve the symptoms and signs of MGD-related dry eye, reduce the inflammatory reaction of MG, restore the gland structure, and indirectly improve the visual quality.